2010
DOI: 10.1021/jp9121744
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Oxidation of Unsaturated Lipids as Sensitized by Flavins

Abstract: Triplet-excited riboflavin ((3)RF*) was found by laser flash photolysis to be quenched by polyunsaturated fatty acid methyl esters in tert-butanol/water (7:3, v/v) in a second-order reaction with k approximately 3.0 x 10(5) L mol(-1) s(-1) at 25 degrees C for methyl linoleate and 3.1 x 10(6) L mol(-1) s(-1), with DeltaH(double dagger) = 22.6 kJ mol(-1) and DeltaS(double dagger) = -62.3 J K(-1) mol(-1), for methyl linolenate in acetonitrile/water (8:2, v/v). For methyl oleate, k was <10(4) L mol(-1) s(-1). For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 87 publications
6
65
0
1
Order By: Relevance
“…The high whey protein presence in milk for example ([Sub] ∼ 5–6 g L −1 ) disfavours such approach, as the amount of flavonoids required would affect flavour quality (astringency), colloidal behaviour, and oxidative stability (prooxidant effects). Lipids, on the other hand, are more readily protected as k I of polyunsaturated fatty acid chains is significantly lower (∼10 5 –10 6 L mol −1 s −1 , depending on the number of unsaturations) …”
Section: Protection Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high whey protein presence in milk for example ([Sub] ∼ 5–6 g L −1 ) disfavours such approach, as the amount of flavonoids required would affect flavour quality (astringency), colloidal behaviour, and oxidative stability (prooxidant effects). Lipids, on the other hand, are more readily protected as k I of polyunsaturated fatty acid chains is significantly lower (∼10 5 –10 6 L mol −1 s −1 , depending on the number of unsaturations) …”
Section: Protection Mechanismsmentioning
confidence: 99%
“…Lipids, on the other hand, are more readily protected as k I of polyunsaturated fatty acid chains is significantly lower (∼10 5 -10 6 L mol −1 s −1 , depending on the number of unsaturations). 78,79 At higher oxygen concentrations, the flavin-mediated photooxidation mechanism shifts to a type II pathway with singlet oxygen formation outcompeting the quenching of excited sensitiser by flavonoids (vide infra). Indeed the rate constant for quenching of triplet-excited riboflavin by oxygen, k II , is very high (∼10 9 -10 10 L mol −1 s −1 ) 35, 36 which, in combination with the high solubility of oxygen in oils or fatty matrices (∼10 mM), makes conditions ideal for a type II process [Eqn (3)].…”
Section: Photoprotection Mechanismmentioning
confidence: 99%
“…Endogenous polyunsaturated chains on sn‐2 position possess cis‐double bonds each separated by one CH 2 group. These hydrogens are very reactive to free‐radical attack, making polyunsaturated fatty acids subject to oxidative modification (Huvaere et al . 2010).…”
Section: Diversity Of Brain Lipidsmentioning
confidence: 99%
“…Radical transport between lipid and proteins has, however, also been suggested to be important for the generation of dityrosine (Saeed et al 2006), and this mechanism seem to be of major importance in cheese (Dalsgaard et al 2010), but no dityrosine generation was found to occur in the cheese-WPI. These results indicate that whey proteins prevented interaction between triplet-excited riboflavin and the highly labile caseins (Huvaere et al 2010) in the cheese-WPI and also prevented interaction between caseins and lipids thus preventing radical transfer from the lipid phase to the casein fraction. The addition of WPI resulted in a lower accumulation of both dityrosine and DMDS indicating that scavenging was not the mechanism responsible for the antioxidative effect of WPI.…”
Section: Discussionmentioning
confidence: 76%